Muscle Activation Patterns During Movement Attempts in Children With Acquired Spinal Cord Injury: Neurophysiological Assessment of Residual Motor Function Below the Level of Lesion - Atkinson, Darryn A.; Mendez, Laura; Goodrich, Natalie; Aslan, Sevda C.; Ugiliweneza, Beatrice; Behrman, Andrea L. (Frontiers in Neurology, 2019)
Introduction Characterization of residual neuromotor capacity after spinal cord injury (SCI) is challenging. The current gold standard for measurement of sensorimotor function after SCI, the International Society for Neurological Classification of Spinal Cord Injury (ISNCSCI) exam, seeks to determine isolated intentional muscle activation, however many individuals with SCI exhibit intentional movements and muscle activation patterns which are not confined to specific joint or muscle. Further, isolated muscle activation is a feature of the neuromuscular system that emerges during development, and thus may not be an appropriate measurement standard for children younger than 6. Methods We utilized neurophysiological assessment methodology, long studied in adult SCI populations, to evaluate residual neuromotor capacity in 24 children with SCI, as well as 19 typically developing (TD) children. Surface electromyography (EMG) signals were recorded from 11 muscles bilaterally, representing spinal motor output from all regions (i.e. cervical, thoracic, and lumbosacral), during standardized movement attempts. EMG records were subjectively analyzed based on spatiotemporal muscle activation characteristics, while the voluntary response index (VRI) was utilized for objective analysis of unilateral leg movement tasks. Results Evidence of intentional leg muscle activation below the level of lesion was found in 11/24 children with SCI, and was classified based on activation pattern. Trace activation, bilateral (generalized) activation, and unilateral or isolated activation occurred in 32%, 49%, and 8% of movement tasks, respectively. Similarly, VRI analyses objectively identified significant differences between TD and SCI children in both magnitude (p<.01) and similarity index (p<.05) for all unilateral leg movement tasks. Activation of the erector spinae muscles, recorded at the T10-T12 vertebral level, was observed in all children with SCI, regardless of injury level or severity. Conclusions Residual descending influence on spinal motor circuits may be present after SCI in children. Assessment of multi-muscle activation patterns during intentional movement attempts can provide objective evidence of the presence and extent of such residual muscle activation, and may provide an indicator of motor recovery potential following injury. The presence of residual intentional muscle activation has important implications for rehabilitation following pediatric-onset SCI.